Factors Associated with Stunting Incidents in Toddlers - Sari Anita; Nesi Novita; Elita Vasra (Poltekkes Kemenkes Palembang, 2023)
Stunting under five is a condition of failure to thrive in children under 5 years old due to chronic malnutrition and recurrent infectious diseases, especially in the first 1,000 days of life. Stunting arises as a result of malnutrition which has accumulated over a long period of time so that its physical manifestations will be more visible at the age of 24–59 months. Based on the framework of the causes of nutritional problems